REMODELLING OF MORPHOLOGICAL AND FUNCTIONAL PARAMETERS OF THE GUMS UNDER THE INFLUENCE OF FOOD ADDITIVES COMPLEX - Bilash, S.M.; Oleksiienko, V.V.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Donchenko, S.V.; Oliinichenko, Y.O. (World of Medicine and Biology, 2025)
Currently, food additives are widely used in the food industry. This is not only because they significantly enhance the taste of products but also because they extend their shelf life. However, their negative effects often become apparent only after sometime. This experiment aimed to examine the impact of various food additives on the gums and changes in their composition. The study revealed that a combination of food additives (monosodium glutamate, sodium nitrite, and Ponceau 4R) affects the microvasculature of rat gums, leading to hemodynamic disturbances and, over time, impairing blood supply to the gums. Morphological changes in microvessels were mainly observed from the fourth week of the experiment, characterized by vasodilation or vasoconstriction and the formation of erythrocyte aggregates. These changes resulted in significant pathological alterations in the structural organization of the gums and their bloods upply, affecting the oral cavity as a whole.
Keywords: oral cavity; pathological changes; gums; mucous membrane; lamina propria; morphometry; periodontium; connective tissue